Управление процессами контактного взаимодействия при пропитке макрогетерогенных композиционных материалов на основе железа - Суховая, Е.В.; Сыроватко, Ю.В. (Вісник Українського матеріалознавчого товариства, 2016)
The phase and structural composition of the interfacial zones between the W–C filler and the Fe–C–B–P–Mo matrix of the composite materials was investigated by quantitative metallographic, X-ray, energy dispersive X-ray, and statistical methods. The peculiarities of a structure formation of the interfaces of dissolution-and-diffusion type were explained based on the regular solution formality taking into account that ion Mo creating non-uniformly charged ion cloud around itself are considered as a local disturbance. The ways to control the intension of the interfacial reactions between the filler and the molten binder under infiltration of composite materials have been recommended.